Acehnese Cultural Fusion Builds Positive Language Views in Young Children - Abdullah, Jannati; Sari, Siti Mayang; Syarfuni, Syarfuni (Academia Open, 2025)
General Background: Language attitudes developed in early childhood are foundational to social integration and identity formation. Specific Background: In culturally rich regions like Aceh, local values are often underrepresented in formal early childhood education. Knowledge Gap: Limited research explores the pedagogical impact of integrating Acehnese culture into language development strategies for young learners. Aims: This study aims to examine the effectiveness of a fusion culture-based learning model in improving language attitudes among early childhood students through the integration of Acehnese cultural elements. Results: Using a case study approach with data gathered via observation, interviews, and document analysis, the study found that embedding traditional games, regional songs, and folklore into thematic lessons significantly enhanced students’ ability to greet, thank, request permission, and interact politely. Novelty: The pedagogical innovation lies in the contextualization of early childhood learning through a fusion of traditional Acehnese cultural expressions and modern educational techniques. Implications: These findings demonstrate that local culture-based learning not only nurtures positive language attitudes but also strengthens cultural identity from an early age, offering a replicable model for culturally responsive early childhood education. Highlights: Enhances polite communication in young learners. Integrates traditional culture with modern pedagogy. Strengthens early cultural identity formation. Keywords: Language Attitudes, Early Childhood, Local Culture, Fusion Learning, Acehnese Education